The Ankle- Brachial Pressure Index AS A Predictor of Coronary Artery Disease Severity - Al Saffar, Hilal B.; Al Ghizzi, Haider J.; Muhammed, Shakir M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Atherosclerosis is a diffuse disease process, being present in one vascular bed predicts its presence in the others. Ankle –brachial pressure index (ABI) is a non invasive test proved to be sensitive and specific in detecting and assessing the severity of peripheral arterial disease.Patients and Methods: One hundred fifty patients (150) were enrolled in this study, from January - June 2007; all were referred to the Iraqi Centre for Heart Diseases (I.C.H.D.) for further evaluation, with request for further assessment of CAD or lower extremity peripheral arterial disease. Clinical data and physical examination were performed; ABI was calculated by measurement of systolic pressure on both ankles over both dorsalis pedis and posterior tibial arteries and on both arms over the brachial arteries by using a Doppler stethoscope. The Ankle –Brachial Pressure Index (ABI) calculation was made by taking the lowest value for the ankle pressure and the highest value for the brachial pressure. The normal value for the ABI range from (1-1.4), a cutoff value of < 0.90 was used to identify low ABI. All patients underwent diagnostic coronary angiography and quantitative coronary angiography (QCA) was used to identify the lesion length and severity of stenosis. The severity of CAD was quantified by GENSINI score, the number of diseased vessels and the number of significant lesions.Results: The mean Ankle-Brachial Pressure index (ABI) for the sample was 0.908±0.31 (range 0- 1.53), the mean GENSINI score was 44.02±40 (range 0-148), GENSINI score was zero in 30 (20%) patients, 40 (26%) were having no diseased vessel, 41(27%) having single, and 43 (28.7%) double and 26 (17%) triple vessel disease. ABI was inversely related to the extent of CAD assessed by GENSINI (p-value 0.015), number of diseased vessels (p-value 0.009), and number of significant lesions (p-value 0.021). ABI < 0.9 was recorded in 51 patients (34%) and a low ABI was an independent factor for a higher GENSINI scores (p-value 0.043) and a higher number of diseased vessels (p-value 0.0001). Patients who were referred with PAD were found to have significantly lower ABI than the rest of the sample (p=0.0001), and a coexisted CAD was detected in 15 out of 20 (75%) patients.Conclusions: ABI was a useful bedside clinical test that predicts the severity of the CAD in patients who are already suffering from or suspected to have ischemic heart disease.